EKSISTENSI PERDAGANGAN VCD/DVD BAJAKAN (Studi Kasus Perdagangan VCD/DVD Bajakan di Jl. Mataram, Yogyakarta) - , HANIK NURSICHAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ABSTRACT Copyright is a form of intellectual property legal basis contained in Undang-undang No. 19 Tahun 2002 . Where in the law is written that copyright is the exclusive right of a creator owned the work produced . But amid the enactment of the law in fact is happening is the tendency of the high level of copyright infringement . One form of copyright infringement is trading VCD /DVD piracy that still survive to this day even done openly and escaped the raid officers. This study aimed to determine the causes of the existence of trade VCD / DVD piracy These factors were seen on the factors that affect law enforcement . That's because the existence of trade VCD / DVD piracy indicates weak law enforcement . Therefore, of the factors that affect the law enforcement can be used as an analysis to determine the causes of the existence of trade VCD / DVD piracy . This study uses descriptive qualitative analysis techniques , to describe the state of research based on the facts on the ground . Data were collected through interviews, observation, and documentation. These results indicate that the existence of trade VCD / DVD pirated especially in Jl Mataram, Yogyakarta is caused by several factors related to the factors that affect law enforcement . According to some experts such factors including the factor of regulation or legislation , law enforcement factors , and community factors . First , when viewed from regulatory factors or laws then problems occur is the absence of implementing regulations of copyright law than the clarity of the rules contained in the law also led to legislation ineffective running . Second , factors law enforcement officers do not have the commitment and consistency in enforcing copyright law . This can be seen from the cooperation between the police forces with producer and trader . Third , community factors , the positive response from the public the existence of pirated products show low levels of understanding and awareness of the law in masyaraka . That led to the high number of inquiries for the product so that the trading of pirated VCD / DVD piracy still survive to this day . Therefore the suggestion that we ask is ( 1 ) implementing regulations should be made in the form of PP with support regulation and regulation of copyright that copyright laws can be effective . ( 2 ) The role of city government is also required to regulate traders who use public areas for trade . ( 3 ) the rule of law , the application of strict sanctions and socialization should be pursued and implemented as a control for the public to refrain from activities misuse of copyright laws